A Variant in the Nicotinic Acetylcholine Receptor Alpha 3 Subunit Gene Is Associated With Hypertension Risks in Hypogonadic Patients - Wu, Tao; Wang, Yujia; Shi, Wei; Zhang, Bi-Qi; Raelson, John; Yao, Yu-Mei; Wu, Huan-Dong; Xu, Zao-Xian; Marois-Blanchet, Francois-Christophe; Ledoux, Jonathan; Blunck, Rikard; Sheng, Jian-Zhong; et al. (Frontiers in Genetics, 2020)
Ephb6 gene knockout causes hypertension in castrated mice. EPHB6 controls catecholamine secretion by adrenal gland chromaffin cells (AGCCs) in a testosterone-dependent way. Nicotinic acetylcholine receptor (nAChR) is a ligand-gated Ca2+/Na+ channel, and its opening is the first signaling event leading to catecholamine secretion by AGCCs. There is a possibility that nAChR might be involved in EPHB6 signaling, and thus sequence variants of its subunit genes are associated with hypertension risks. CHRNA3 is the major subunit of nAChR used in human and mouse AGCCs. We conducted a human genetic study to assess the association of CHRNA3 variants with hypertension risks in hypogonadic males. The study cohort included 1,500 hypogonadic Chinese males with (750 patients) or without (750 patients) hypertension. The result revealed that SNV rs3743076 in the fourth intron of CHRNA3 was significantly associated with hypertension risks in the hypogonadic males. We further showed that EPHB6 physically interacted with CHRNA3 in AGCCs, providing a molecular basis for nAChR being in the EPHB6 signaling pathway.